Pembuatan buku teks pelajaran terintegrasi pembelajaran kontekstual dan literasi lingkungan materi gelombang dan alat optik untuk siswa SMA kelas XI - Salma Amalia As Shidiq; Yenni Darvina; Asrizal Asrizal; Desnita Desnita (PILLAR OF PHYSICS EDUCATION, 2020)
Education in 21th century is the education with the learning system which used the environment as a medium of learning. The students are relating, experiencing, applying the phenomena that happen around the students. The students is cooperated in finding phenomenon and could transfer to another science. One of learning strategy that used is contextual learning and strengthening student environmental literacy. the purposed of the research is for validating and practicability of text book to be used. The type of this research is Research and Development. The object of research is integrated contextual learning-environmental literacy textbooks. The instrument of data collection is conducted by filling in the contextual learning questioner sheet, validating questioner sheet by physics lecturer, and practicality sheet by teacher and students. Based on data analysis, the results obtained that integrated contextual learning-environmental literacy textbooks which have validated by the experts has the average of 88 which is in the excellent category.  Then, the practicability test of the textbook according to the teachers has the average of 92.5 and according to the students are 84.